Replication of Structured DNA and its implication in epigenetic stability - Cea, Valentina; Cipolla, Lina; Sabbioneda, Simone (Frontiers in Genetics, 2015)
DNA replication is an extremely risky process that cells have to endure in order to correctly duplicate and segregate their genome. This task is particularly sensitive to DNA damage and multiple mechanisms have evolved to protect DNA replication as a block to the replication fork could lead to genomic instability and possibly cell death. The DNA in the genome folds, for the most part, into the canonical B-form but in some instances can form complex secondary structures such as G-quadruplexes (G4). These G rich regions are thermodynamically stable and can constitute an obstacle to DNA and RNA metabolism. The human genome contains more than 350000 sequences potentially capable to form G-quadruplexes and these structures are involved in a variety of cellular processes such as initiation of DNA replication, telomere maintenance and control of gene expression. Only recently, we started to understand how G4 DNA poses a problem to DNA replication and how its successful bypass requires the coordinated activity of ssDNA binding proteins, helicases and specialized DNA polymerases. Their role in the resolution and replication of structured DNA crucially prevents both genetic and epigenetic instability across the genome.